2007
DOI: 10.1631/jzus.2007.b0638
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a high frequency of chromosomal rearrangements in the centromeric regions of prostate cancer patients

Abstract: Abstract:The aim of the present investigation was to study the major chromosomal aberrations (CA) like deletion, translocation, inversion and mosaic in prostate cancer patients of Tamilnadu, Southern India. Totally 45 blood samples were collected from various hospitals in Tamilnadu, Southern India. Equal numbers of normal healthy subjects were chosen after signing a consent form. Volunteers provided blood samples (5 ml) to establish leukocyte cultures. Cytogenetic studies were performed by using Giemsa-banding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…As such, a recent study has demonstrated that HP1 variants display decreased expression levels in prostate cancer cell lines and prostate cancer tissues compared to normal tissues 32. In addition, an elevated frequency of chromosomal rearrangements is observed in the centromeric regions of prostate cancer patients,33 which is consistent with the loss of centromeric integrity associated with decreased levels of HP1 and heterochromatin stability. To investigate a potential involvement of KDM2A in prostate cancer, we searched the Oncomine on-line databases for differential KDM2A expression in normal versus tumorigenic prostate tissues.…”
Section: Resultsmentioning
confidence: 76%
“…As such, a recent study has demonstrated that HP1 variants display decreased expression levels in prostate cancer cell lines and prostate cancer tissues compared to normal tissues 32. In addition, an elevated frequency of chromosomal rearrangements is observed in the centromeric regions of prostate cancer patients,33 which is consistent with the loss of centromeric integrity associated with decreased levels of HP1 and heterochromatin stability. To investigate a potential involvement of KDM2A in prostate cancer, we searched the Oncomine on-line databases for differential KDM2A expression in normal versus tumorigenic prostate tissues.…”
Section: Resultsmentioning
confidence: 76%
“…13 The latter resides in the long arm of chromosome 9 that is frequently deleted in human cancers. 14, 15, 16 This prompted us to investigate whether the deletion of that region caused miR-204 downregulation in gastric tumoral tissues. To this end, we evaluated the presence of TRPM3 gene loss using a PCR-based test termed Multiplex Ligation-dependent Probe Amplification.…”
Section: Resultsmentioning
confidence: 99%
“…Sushma T.A., 5 found that out of 65 cases serum PSA values over 10ng/ml were seen in 10 benign (16.6%) cases and 3 malignant (60%) cases. V. Balachandar et al 6 in 2007,noted in his study that out of total 45 prostate cancer patients, PSA level of collected blood samples was ≤ 10.0 ng/ml in 39 subjects (86.7%) and ≥10.0 ng/ml in 6 subjects (13.3%). V. Balachandar et al 1 in 2008, found that range of PSA values in Prostate Cancer patients were 8 to 12 ng/ml.…”
Section: Discussionmentioning
confidence: 93%
“…The most frequent losses were on chromosomes 2, 5, 6, 8, 10, 13, 15, and 16. V. Balachandar et al, 6 in 2007, found that among 45 blood samples from prostate cancer patients, major chromosomal aberrations like deletion, translocation, inversion seen in chromosomes 1, 3, 5, 6, 7, 9, 13, 16, 18 and X and mosaic were identified in patients. V. Balachandar et al, 1 in 2008, studied 18 prostate cancer patients and found that chromosome 1, 2, 3 6, 7, 9, 16, 22, and X were the affected chromosome in Prostate Cancer patients.…”
Section: Discussionmentioning
confidence: 99%